PEMBERDAYAAN MASYARAKAT BERBASIS HUTAN RAKYAT DALAM MEMELIHARA KELESTARIAN HUTAN (Studi Kasus Pada Kelompok Masyarakat Gaharu di Kelurahan Pekan Bahorok, Kecamatan Bahorok, Kab. Langkat) - Muhammad Reza Ardillah (Perspektif Sosiologi, 2012)
Abstract Indonesia is a country rich in forest resources. Utilization of forest resources for the community is very important, especially the community around the forest area. Social Forestry is a method that has long used by countries in the world to manage their forests. Indonesian Ministry of Forestry also apply through social forestry to manage Indonesia’s forests and forest communities use for the one with the empowerment of the poeple of forest-based communities. This research was conducted in Village Fair Bahorok, District Bahorok, Langkat District. This location is directly adjecant to Forest Gunung Leuser Park (TNGL). The informant is divided into two key informants that KEMAGAHAN chairmain and members of the group and regular informant that NGO, Langkat Forestry Office and The Center for Conservation TNGL. The results showed that KEMAGAHAN was formed by the local community. Community was aware that they have the potential forest area that can be used one Pohon Gaharu. They cultivated up these plants by way of self-help and the end result is to increase income of local communities participate in the establishment and preservation forest plants. Keyword : community empowerement, social forestry, local institution